Pengaruh Fermentasi Pada Berbagai Media Porous Pada Aplikasi Penanaman Wall Gardening Tanaman Seledri (Apium graveolens L.) Sebagai Model Budidaya Urban Farming - Jofita, Dinda Dara; Mardiyani, Siti Asmaniyah; Murwani, Indiyah (Folium : Jurnal Ilmu Pertanian, 2025)
Wall gardening is a matching method of planting that utilizes walls both inside and outside the room. This urban farming model has become a trend in various urban areas. This study aims to find out the impact of the interaction of the composition of the growing media and the fermentation of the plant media on the growth, yield and quality of celery crops. (Apium graveolens L.). This study uses Factorial Group Random Planning (RAK). The first factor is the composition of various porous plant media (raw rice husks, rice husks charcoal, volcanic sands, cocopeat, chopped fern, andam, manure) (M) with 4 different compositions (M1 = 5: 0,5:2:0,5:0,5::0,5:5:0,5), (M2 = 3:1:1:1:2:1:1), ( M3 = 1:1:1:1:1:1) (M4 = 5:1:0,5:1:1:0), the second factor is fermentation of plant media. (F1 fermentation dan F2 non fermentation). The results of the study show that the treatment of composition of plant media (M) and fermentation of plant medium (F) only affects the variable length of plant and the number of leaf stems. Generally speaking, M3 treatment (porous plant media composition 1:1:1:1:1:1) is a medium composition that has the best growth, yield and quality compared to other compositions. Fermentation on the growing medium only affects the number of breeds and number of leaf sticks.